(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the scientific and methodological foundations for enhancing the vocabulary, clarifying word meanings, and activating the lexicon of primary school students. The process of vocabulary development is investigated based on the principles of cognitive psychology and linguodidactics, identifying four primary dimensions of speech development. Drawing on textbook materials, the article substantiates the methods for uncovering semantic facets of words and evaluates the effectiveness of lexico-logical exercises.